Yang-Mills propagators in linear covariant gauges from Nielsen identities - Napetschnig, Martin; Alkofer, Reinhard; Huber, Markus Q.; Pawlowski, Jan M. (Physical review, 2021)
We calculate gluon and ghost propagators in Yang-Mills theory in linear covariant gauges. To that end, we utilize Nielsen identities with Landau gauge propagators and vertices as the starting point. We present and discuss numerical results for the gluon and ghost propagators for values of the gauge parameter 0 < xi <= 5. Extrapolating the propagators to xi -> infinity, we find the expected qualitative behavior. We provide arguments that our results are quantitatively reliable at least for values xi <= 1/2 of the gauge-fixing parameter. It is shown that the correlation functions, and, in particular, the ghost propagator, change significantly with increasing gauge parameter. In turn, the ghost-gluon running coupling as well as the position of the zero crossing of the Schwinger function of the gluon propagator remain within the uncertainties of our calculation unchanged.